Pengaruh Pelatihan Pendidikan Karakter Terhadap Self Confidence Mahasiswa Di Akper “YKY” Yogyakarta - Tenang Aristina; Shanti Wardhaningsih; Moh Affandi (Journal of Health (JoH), 2018)
Background : The problem of self confidence in student should be a common concern considering that we are now in global era that free for competition with countries in the world. It requires a character that is self confident that will deliver the students to have a strong believe and motivation to dare to compete with the people of various countries. Purpose : Determining the influence of character education modul of attitude and self confidence competences on the students. Research method : This research design was quasy experiment with pre-post test design. The sample were total sampling. There were 68 of population at the first year divided into two class. Class 1a was 34 students as a control group and class 1b was 34 students as a intervention group. The variable of attitude and self confidence was measured with Wilcoxon sign rank test and Mann-Whitney test. Result : The result showed that an increase on self confidence variable by application of character education modul. Statistic analysis ρ=0,009 on attitude variable of intervention group and ρ=0,317 on control group. On self confidence variable for intervention group ρ=0,001 and control group ρ=0,063. Differences of self confidence ρ=0,025. Conclusion : The coaching of character education modul was able to elevate the self confidence on students. There was significant changes on self confidence at intervention and control group.